2010
DOI: 10.1002/cncr.25125
|View full text |Cite
|
Sign up to set email alerts
|

CFL1 expression levels as a prognostic and drug resistance marker in nonsmall cell lung cancer

Abstract: BACKGROUND: Nonsmall cell lung cancer (NSCLC) is the major determinant of overall cancer mortality worldwide. Despite progress in molecular research, current treatments offer limited benefits. Because NSCLC generates early metastasis, and this behavior requires great cell motility, herein the authors assessed the potential value of CFL1 gene (main member of the invasion/metastasis pathway) as a prognostic and predictive NSCLC biomarker. METHODS: Metadata analysis of tumor tissue microarray was applied to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 91 publications
4
45
0
3
Order By: Relevance
“…Therefore, CFL1 immunohistochemical expression is specific to PCa, and is associated with the aggressiveness of the phenotype. This is consistent with a number of studies that have reported CFL1 to be associated with a more aggressive phenotype and with tumor progression in various solid tumor tissues (12)(13)(14)(15). For instance, CFL1 has been reported to play a major role in tumor progression in ovarian carcinomas, as nearly 64% of all ovarian tumors are positive for CFL1 (16), upregulation of phosphorylated CFL1 levels result in increased chemoresistance (17) and the patients with CFL1-positive tumors demonstrate decreased progression-free survival rates compared with the patients with CFL1-negative lesions (18).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, CFL1 immunohistochemical expression is specific to PCa, and is associated with the aggressiveness of the phenotype. This is consistent with a number of studies that have reported CFL1 to be associated with a more aggressive phenotype and with tumor progression in various solid tumor tissues (12)(13)(14)(15). For instance, CFL1 has been reported to play a major role in tumor progression in ovarian carcinomas, as nearly 64% of all ovarian tumors are positive for CFL1 (16), upregulation of phosphorylated CFL1 levels result in increased chemoresistance (17) and the patients with CFL1-positive tumors demonstrate decreased progression-free survival rates compared with the patients with CFL1-negative lesions (18).…”
Section: Discussionsupporting
confidence: 93%
“…CFL1 and destrin are both actin-depolymerizing proteins and are involved in the organization of the cytoskeleton. A number of authors have reported CFL1 and destrin differential expression in cancer cells (13,(22)(23)(24)(25). To the best of our knowledge, we report for the first time their function related with drug resistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 66%
“…The spontaneous overexpression of CFL1 may be detected in invasive sub-populations of breast tumor cells in rats, as well as in biopsies of oral, renal, non-small cell lung cancer (NSCLC) and ovarian carcinoma. High CFL1 levels are correlated with lower overall survival rates and resistance to several alkylating drugs in NSCLC patients (13,(23)(24)(25). The overexpression of CFL was also detected in cisplatin-resistant cells (13).…”
Section: Discussionmentioning
confidence: 96%
“…These results were corresponded * Results are shown as a range of the data obtained for identified proteins from different samples. to the data of Davila et al [40] who at comparative study of proteins of BPH-1 and PC-3 cells did not detect any changes in the level of Cofilin 1, though the increased expression of Cofilin 1 was observed in the cells of colorectal and lung cancer [21,30].…”
Section: Comparative Analysis Of Protein Fractionsmentioning
confidence: 72%